Commodity Markets Outlook, October 2021 - World Bank Group (World Bank, Washington, DC, 2021)
Commodity prices have risen to high levels by historical standards. Energy prices have increased sharply, especially for natural gas and coal, while most non-energy prices have plateaued after steep increases earlier in the year. Crude oil prices are forecast to average $74/bbl in 2022, up from a projected $70/bbl in 2021. After registering more than 48 percent increase this year, metal prices are projected to decline 5 percent in 2022. Agricultural prices, which are projected to rise more than 20 percent this year, are expected to broadly stabilize in 2022. These forecasts are subject to substantial risks, from adverse weather, further supply constraints, or additional outbreaks of COVID-19. Energy prices are particularly at risk of additional volatility in the near-term given low inventory levels. A Special Focus section explores the impact of urbanization on commodity demand. Although cities are often associated with increased demand for energy commodities (and hence greenhouse gas emissions) the report finds that high-density cities, particularly in advanced economies, can have lower per capita energy demand than low-density cities. As the share of people living in urban areas is expected to continue to rise, these results highlight the need for strategic urban planning to maximize the beneficial elements of cities and mitigate their negative impacts.